1986
DOI: 10.1152/ajpheart.1986.250.5.h861
|View full text |Cite
|
Sign up to set email alerts
|

Thyroidectomy of SHR: effects on ventricular relaxation and on SR calcium uptake activity

Abstract: Ventricular hypertrophy and hypothyroidism are each characterized by impaired cardiac muscle relaxation and sarcoplasmic reticulum (SR) calcium uptake activity. A previous report also showed that hypothyroidism does not reverse ventricular hypertrophy (left-to-right ventricular weight ratios) of spontaneously hypertensive rats (SHR). We characterized the effects of thyroidectomy of 8 wk duration on relaxation of ejecting hearts and on SR calcium uptake activity from SHR and nonhypertrophic Wistar-Kyoto rat (WK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1

Year Published

1987
1987
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
3
14
1
Order By: Relevance
“…The T r variable did not correlate as well because it differed between nondiabetic SHR and WKY rat groups, whereas the SR Ca 2+ uptake activity did not (Tables 4 and 5). In contrast to the results of the previous report, 16 in the present study LV-dP/dt varied with P^A , . However, the former variable is inconsistent and difficult to interpret, largely because of its dependence on the configuration of the pressure wave.…”
Section: -13contrasting
confidence: 99%
See 3 more Smart Citations
“…The T r variable did not correlate as well because it differed between nondiabetic SHR and WKY rat groups, whereas the SR Ca 2+ uptake activity did not (Tables 4 and 5). In contrast to the results of the previous report, 16 in the present study LV-dP/dt varied with P^A , . However, the former variable is inconsistent and difficult to interpret, largely because of its dependence on the configuration of the pressure wave.…”
Section: -13contrasting
confidence: 99%
“…A recent report from this laboratory suggested that the ratio P^A , can serve as an index of load-dependent relaxation in the ejecting ventricle. 16 As expected, the value of Pmu/Ar in the present study correlated with the rate of SR Ca 2+ uptake between experimental groups (Table 5, Figures 2 and 3). The T r variable did not correlate as well because it differed between nondiabetic SHR and WKY rat groups, whereas the SR Ca 2+ uptake activity did not (Tables 4 and 5).…”
Section: -13supporting
confidence: 87%
See 2 more Smart Citations
“…These findings have led to the hypothesis that enhancement of myocardial contractility by thyroid hormones is the result of increased cardiac myosin ATPase ac-tivity. However, thyroid hormone has also been reported to alter Ca uptake by sarcoplasmic reticulum (9)(10)(11)(12)(13)(14), to stimulate plasma membrane Ca-ATPase activity (4,15,16), and also to increase the numbers of sarcolemmal sodium pump sites (17)(18)(19). Therefore, the mechanisms by which myocardial contractility is enhanced in response to thyroid hormone appear to include altered Ca handling by sarcoplasmic reticulum and also changes in sarcolemmal membrane function that would directly influence the excitation-contraction coupling process.…”
Section: Introductionmentioning
confidence: 99%